Developing an orthography for Onya Darat (western Borneo); Practical and theoretical considerations - Tadmor, Uri (Wacana, Journal of the Humanities of Indonesia, 2009)
Onya Darat is a language spoken, with great dialectal variation, in the interior of western Borneo. It is the southernmost member of Land Dayak, a branch of the Austronesian language family. This article reports on the development of a writing system for Onya Darat. In addition to five vowels and 19 simple consonants, Onya Darat also exhibits three series of complex oral-nasal segments: prenasalized oral stops, preoralized nasals, and postoralized nasals. An analysis of the Onya Darat sound system reveals that of these three series only postoralized nasals are distinctive and therefore need to be represented in the writing system. The proposed orthography, developed with the aid of native speakers, represents all and only the phonemes of Onya Darat without resorting to diacritics or special characters.